1994
DOI: 10.1902/jop.1994.65.3.244
|View full text |Cite
|
Sign up to set email alerts
|

Guided Tissue Regeneration With and Without Decalcified Freeze‐Dried Bone in Mandibular Class II Furcation Invasions

Abstract: The purpose of this study was to compare periodontal soft and hard tissue repair using expanded polytetrafluoroethylene (ePTFE) membranes with and without decalcified freeze-dried cortical bone allografts (DFDBA). Six patients with 17 mandibular Class II buccal molar furcal invasions received oral hygiene instructions followed by scaling and root planing. Baseline soft tissue measurements with periodontal probes were made to assess probing depths (PD), recession (REC), and probing attachment levels (PAL). Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 29 publications
3
50
1
Order By: Relevance
“…GTR with either decalcified freeze-dried bone allograft (Anderegg et al, 1991) or composite grafts of autografts and tricalcium phosphate and/or demineralized freeze-dried bone allografts (Schallhorn and McClain, 1988) showed substantially more bone fill on re-entry in comparison with other studies (Wallace et al, 1994;Becker et al, 1995) which have shown no real benefit of the combination of GTR and grafting material. Caffesse et al (1993) reported results of treatment of furcation defects in beagle dogs, with and without demineralized freeze-dried cortical bone grafts, in a GTR procedure and found that the use of the guided tissue regeneration procedure resulted in an increase in connective tissue and alveolar bone regeneration, but that adjunctive bone grafting in itself did not appear to enhance regeneration.…”
Section: (B) Guided Tissue Regenerationmentioning
confidence: 87%
See 2 more Smart Citations
“…GTR with either decalcified freeze-dried bone allograft (Anderegg et al, 1991) or composite grafts of autografts and tricalcium phosphate and/or demineralized freeze-dried bone allografts (Schallhorn and McClain, 1988) showed substantially more bone fill on re-entry in comparison with other studies (Wallace et al, 1994;Becker et al, 1995) which have shown no real benefit of the combination of GTR and grafting material. Caffesse et al (1993) reported results of treatment of furcation defects in beagle dogs, with and without demineralized freeze-dried cortical bone grafts, in a GTR procedure and found that the use of the guided tissue regeneration procedure resulted in an increase in connective tissue and alveolar bone regeneration, but that adjunctive bone grafting in itself did not appear to enhance regeneration.…”
Section: (B) Guided Tissue Regenerationmentioning
confidence: 87%
“…Caffesse et al (1993) reported results of treatment of furcation defects in beagle dogs, with and without demineralized freeze-dried cortical bone grafts, in a GTR procedure and found that the use of the guided tissue regeneration procedure resulted in an increase in connective tissue and alveolar bone regeneration, but that adjunctive bone grafting in itself did not appear to enhance regeneration. In a study of six patients with 17 Class II furcal defects, Wallace et al (1994) compared soft and hard tissue repair using e-PTFE membranes with and without decalcified freezedried cortical bone allografts (DFDBA). These investigators reported that addition of DFDBA to the GTR procedure did not improve mean closed and open probing measurements in terms of repair.…”
Section: (B) Guided Tissue Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Wallace et al 41) also reported that there was no difference between GTR with e-PTFE membrane and GTR with e-PTFE membrane combined with the DFDB in the bifurcation area. This present study had consistent results with the previously mentioned Bowers 42,43) and Anderegg's study 14) , in which bone graft material could support the barrier material and prevent its collapse, and eventually promote bone regeneration.…”
Section: A At 4 Weeksmentioning
confidence: 97%
“…However, predictable regeneration cannot be achieved in advanced furcation invasions due to the complexity of furcation morphology [4]. Multiple modalities have been utilized over the years ranging from non-surgical therapy [3], surgical therapy utilizing regenerative methods using grafts and membranes [5,6,7] , root resection [8 ], tunnel procedure [9] with unpredictable success. The patients are most often offered options which are unpredictable, more invasive and expensive.…”
Section: Introductionmentioning
confidence: 99%